"For Such Purposes As": Towards an embedded and embodied understanding of torture's purpose. (1st January 2021) - Cakal, Ergün
Abstract : Purpose is a constitutive element of torture under article 1 of the UN Convention Against Torture (UNCAT). It is increasingly and widely accepted as being the determinative aggravating factor differentiating between torture and forms of cruel, inhuman and degrading treatment or punishment (hereafter "CIDTP" or "ill-treatment"). Compared to the depth of discussion on other constitutive elements such as severity of pain and suffering and official capacity, the dimensions of purpose have remained relatively and unduly overlooked in scholarship on torture. As the significance of purpose as differentiator becomes increasingly established, there is a corresponding need to better understand its dimensions—particularly to question the rationale for having it mark an aggravation of state violence. This paper will draw and build upon the literature and jurisprudence pertaining to a functionality-oriented, teleological construction of torture, before situating the discussion in torture's broader ecology in order to critically examine and expand understandings of its purpose, bottom-up, situationally and institutionally.